101k views
3 votes
7(3 + x) - 4(x + 1)
distributive property

User Mitenka
by
4.3k points

2 Answers

5 votes

Answer: 17+3x

Explanation:

7(3 + x) - 4(x + 1)=

21+7*x-4x+(-4*1)= ==> Distribution Property

21+7x-4x+(-4)=

21+3x-4=

21-4+3x=17+3x

User Triangle
by
5.4k points
2 votes
Let’s rewrite the expression out:

7(3 + x) - 4(x + 1)

Now we can distribute:

21 + 7x - 4x - 4

Now we can combine like terms:

17 + 3x

Now we flip them around; the coefficient always should come first:

3x + 17

Using the distributive property, the final expression is 3x + 17.

User Ksusha
by
5.1k points